Asupan Vitamin C dan E Dengan SQ-FFQ terhadap Fungsi Paru Perokok dan Non-Perokok - Siska Rian Pratiwi; Amelia Lorensia; Rivan Virlando Suryadinata (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Cigarette smoke is one of exogenous free radical source which causes cell damage to make a decrease oflung function happen. Vitamin C and E are antioxidants which can obstruct the activity of oxidant compounds. Thepurpose of this research was to know the distinction of lung function, Vitamin C and E intake on active and nonsmoker; the influence of vitamin C and E intake towards the lung function. The research design was cross sectional.The measured variables consisted of Vitamin C and E intake by semi quantitative-food frequency questionnaire(SQ-FFQ) as well as the lung function by handheld spirometer. The sampling of this research consisted of 63samples of smokers and 63 samples of non-smoker. The test results showed lung function and vitamin C intake wassignificantly different (p=0,00), while vitamin E (p=0,29) intake did not differ significantly between active smokerand non smoker. The results showed the influence Vitamin C (p=0,00; r=0,63) and Vitamin E (p=0,015; r=0,22)intake towards the lung function. There are differences in vitamin C and E intake, the lung function of smoker andnon smoker; and the influence of Vitamin C and E intake towards the lung function.